SUPREMACY OF SYMBIOSIS? THE GENDERED AFFORDANCES OF EMBODIED TECHNOLOGY DESIGN - Wissinger, Elizabeth (AoIR Selected Papers of Internet Research, 2023)
How do gendered power structures colonize wearable tech and biodesign practice? This paper contends that it is not just the practitioner’s gender, but the gender of the practice itself, that affects the sense of the body being designed for, as well as design goals. Drawing on participant observation and interview data from the wearable tech and biodesign communities, this analysis explores the concrete effects of symbolic gender dichotomies on wearable tech and biodesign practices and outcomes. Extending critical race and technology studies’ claim that design settings’ lack of diversity can lead to biased outcomes, it looks at the lack of diversity in design methods, especially regarding gendered design practices, such as sewing or knitting, in the realm of embodied technology. It examines gendered assumptions in both digital wearable tech, and biodesign, which incorporates living organisms into its function, such as weaving conductive protein nano-wires into mushroom grown textiles. The paper shares three key findings. First, gendered meanings in personnel encounters affected who is considered an expert; female engineers and designers told of having to dress and talk like a man to be taken seriously. Second, less value is accorded to ‘feminine’ ways of making such as knitting, even though these practices can create more cooperative, comfortable, less harmful user/device interactions. Finally, mapping feminine and masculine-oriented design concerns and practices onto post-human or trans-human frameworks, reveals how masculine associated techno/supremacist ideals contrast with feminist informed symbiotic interdependencies between user and technology, which produce designs that envision a more equitable technological future.